Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes productivity in the Eastern Caribbean Currency Union by exploring two complementary exercises. It computes total factor productivity by extending standard growth accounting frameworks with (1) the impact of natural disasters on the stock and productivity of physical capital; (2) human capital accumulation; and (3) the impact of out-migration on labor and human capital. The paper also analyzes labor productivity, including across economic sectors. The results indicate that the historical deceleration in growth was driven mostly by the declining contribution of total factor productivity, which resulted in stagnation in the aftermath of the global financial crisis. Labor productivity measures show that labor is largely allocated in the sectors with relatively lower productivity.